The Value Relevance of Reputation for Sustainability Leadership - Lourenço, Isabel Costa; Callen, Jeffrey Lawrence; Branco, Manuel Castelo; Curto, José Dias (2014)
This study investigates whether the market valuation of the two summary accounting measures, book value of equity and net income, is higher for firms with reputation for sustainability leadership, when compared to firms that do not enjoy such reputation. The results are interpreted through the lens of a framework combining signalling theory and resource-based theory, according to which firms signal their commitment to sustainability to influence the external perception of reputation. A firm’s reputation for being committed to sustainability is an intangible resource that can increase the value of a firm’s expected cash flows and/or reduce the variability of its cash flows. Our findings are according to expectations and show that the net income of firms with good sustainability reputation has a higher valuation by the market, when compared to their counterparts.
Keywords: Value relevance; Reputation; Corporate Sustainability